Costa Rica - Araya Ramírez, Jéssica; Ramírez Molina, Catalina (Universidad de Costa Rica, 2020)
This article summarizes the findings of the research study "Pre-service teacher training in early grade literacy (EGL) for the Primary Education major at the University of Costa Rica", specifically the one taught at the Rodrigo Facio branch. The study analyzed EGL pre-service teacher training, was conducted with a qualitative-descriptive methodology and took place from July 2018 to July 2019. Data were collected and analyzed based on the triangulation of information obtained from three sources: (1) mapping of pre-service teacher training curricula in the area of EGL including eleven courses covering the following three dimensions: Child Development, Knowledge of EGL Content and Evaluation of Learning; (2) eight interviews with teacher trainers and twelve interviews with teachers-in-training; and (3) five observations of university classrooms. The study results suggest that the link between the pre-service training programs, the classroom practice developed by the teacher trainers, and the practical knowledge required by the teachers-in-training to teach EGL requires greater integration and articulation. The implications of these findings need to be reviewed and analyzed by those who coordinate the Primary Education degree and those who serve as teacher educators. It is necessary to align course curricula to what evidence recommends for effective development of literacy skills in this century.